1991
DOI: 10.1111/j.1471-4159.1991.tb11432.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the Myelin‐Associated Glycoprotein in Cultures of Immortalized Schwann Cells

Abstract: Although the myelin-associated glycoprotein (MAG) cannot be detected in primary cultures of rat Schwann cells in the absence of neurons, MAG expression was demonstrated in some lines of cultured Schwann cells that had been immortalized by repetitive passaging. Radioimmunoassay of one such Schwann cell line, S-16, showed a remarkably high MAG concentration of about 1 ng/microgram of total protein, a level that is comparable to the MAG concentration in adult sciatic nerve. The S-16 cells divide very rapidly, are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 40 publications
2
32
0
Order By: Relevance
“…PMP22, MPZ, and SOX10) (22)(23)(24). Briefly, we cloned each genomic segment upstream of a minimal promoter directing the expression of a firefly luciferase reporter gene (25).…”
Section: Mtmr2-mcs3 Displays Strong Enhancer Activity In Cultured Schmentioning
confidence: 99%
See 1 more Smart Citation
“…PMP22, MPZ, and SOX10) (22)(23)(24). Briefly, we cloned each genomic segment upstream of a minimal promoter directing the expression of a firefly luciferase reporter gene (25).…”
Section: Mtmr2-mcs3 Displays Strong Enhancer Activity In Cultured Schmentioning
confidence: 99%
“…Immortalized rat Schwann cells (S16) (22), mouse spinal motor neurons (MN-1) (26), and HeLa cells were grown under standard conditions in DMEM with 10% fetal bovine serum, 2mM L-glutamine, 50 U/ml penicillin, and 50 g/ ml streptomycin. For luciferase assays, $1Â10 4 S16 or MN-1 cells were plated in each well of a 96-well plate.…”
Section: Cell Culture Transfection and Luciferase Assaysmentioning
confidence: 99%
“…The basic premise of SILAC is that two populations of cells are grown in medium containing either unlabeled amino acids or an amino acid containing deuterium or 13 C substitutions. After a suffi-cient incubation period to completely incorporate the labeled amino acid into the cellular proteome, one population of the cells serves as a control and the other is subjected to treatment.…”
mentioning
confidence: 99%
“…Immortalized S16 Schwann cells [3,4] were grown on 150-mm dishes (Falcon) in DMEM supplemented with 10 % fetal bovine serum and 50 Ìg/ml of gentamycin at a density of more than 3.4 ! 10 4 cells/cm 2 .…”
Section: Isolation Of Fractions Enriched In Plasma Membranes From Higmentioning
confidence: 99%
“…They include interactions with the axon and basal lamina, rate of cell division, growth factors, cAMP levels and transcription factors [1,2]. Immortalized Schwann cell lines (S16 and S42) expressing myelin-associated glycoprotein (MAG), PO glycoprotein and galactocerebroside have been generated in our laboratory [3] and in many ways biochemically resemble Schwann cells at an early stage of differentiation toward myelin formation [4]. Previous examination of the cells under different conditions of growth showed that high levels of MAG, PO and their messenger RNAs correlated with decreased proliferation brought about by serum deprivation and with increased cell density [5].…”
Section: Introductionmentioning
confidence: 99%